The Pecten Oculi: An Enigma in Comparative Ophthalmology - Ringvold, Amund (European Journal of Applied Sciences, 2023)
Purpose: To summarize and evaluate the latest hypotheses on the function of the pecten oculi (PO). Methods: Review of relevant literature. Results: The PO is an organ present in all avian eyes. A similar structure, the conus papillaris (CP), is also found in terrestrial reptiles. Several reports have claimed the PO nourishes the avascular avian retina, but it has also been argued that the function is not primarily nutritive but instead may be related to intraocular pH-regulation, as the avian retina has an anaerobic metabolism. These conclusions are, at first glance, contradictory. However, a recent report indicated how these two views may be incorporated in a new and unifying hypothesis, with the common denominator being that the CP/PO evolved in tandem with increasing uric acid (UA) in serum. Discussion: According to Wingstrand and Munk, the PO leaks oxygen and nutrients to the retina, meaning that leakage of the small and heavily soluble component UA in serum could follow the same path. Protein-binding of the UA is not an option in the vitreous body, as the UA could crystalize intraocularly and harm the visual function. Two mechanisms countering this situation have been identified: 1) The inflow of the UA to the intraocular compartments (i. e. - vitreous body and anterior chamber) is reduced through selective barriers both in the PO and in the ciliary body. 2) The UA solubility is increased through alkalization of the vitreous body by the PO. Conclusion: During evolution vision was improved when the retinal vessels were collected in the PO. Two competing hypotheses on the PO’s function have been summarized, and it is shown how these may be incorporated in a new unifying hypothesis.